Finite Element Verification of Saint-Venant Principle based on Abaqus - Dong, Xin; Chen, Juannong (Scientific Journal of Technology, 2026)
The Saint-Venant principle is a classical theory in solid mechanics. The core idea is that the influence of external force on the internal stress and deformation of the solid will gradually weaken to be negligible away from the load area. In this paper, Abaqus finite element software is used to establish a three-dimensional model to study the influence of different load distribution ( point load, line load and uniform load ) on the stress field. The cube model is selected as the analysis object, and the concentrated load and uniform distribution load are applied. By analyzing the stress distribution far away from the load area, it is observed whether it conforms to the conclusion of Saint-Venant principle. The results show that the distribution of stress and deformation tends to be stable when far away from the load area, which is independent of the load form, and further supports the theoretical basis and engineering application value of the Saint-Venant principle.